Georgia : First and Second Reviews Under the Stand-By Arrangement and Under the Standby Credit Facility Arrangement, and Request for Waiver of Nonobservance of Performance Criterion-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Georgia. (IMF Staff Country Reports; Country Report, 2013)
The new government is committed to prudent macroeconomic policies and to enhancing Georgia's business-friendly environment. Large external liabilities plus its high current account deficit remain the main sources of vulnerability, and reducing these in an orderly manner is a key macroeconomic challenge. Greater exchange rate flexibility should help align its monetary policy and exchange rate decisions more closely with its inflation. Maintaining central bank independence and increasing monetary policy transparency are welcomed by the Executive Directors. The impressive structural agenda aims at improving the business environment and at boosting competitiveness.